2017
DOI: 10.1016/j.aogh.2016.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Planned Home Visits of Intern Public Health Nurses: An Example from Turkey

Abstract: Planned and continuous home visits by intern public health nurses resulted in positive health achievements in families, especially for women and children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Other studies which evaluated students' experiences with home visits have shown that students provided training and consultancy to families; they have had the opportunity to improve their knowledge and teamwork skills and to observe the families to whom they provided care in the home environment and they now feel more independent (6,13,14). As the students planned and conducted the home visits with the families during the public health field practice, they may have felt more independent by adopting the manager and planner roles.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies which evaluated students' experiences with home visits have shown that students provided training and consultancy to families; they have had the opportunity to improve their knowledge and teamwork skills and to observe the families to whom they provided care in the home environment and they now feel more independent (6,13,14). As the students planned and conducted the home visits with the families during the public health field practice, they may have felt more independent by adopting the manager and planner roles.…”
Section: Discussionmentioning
confidence: 99%